Whitescapes: A posthumanist political ecology of Alpine migrant (im)mobility. (January 2022) - Pallister-Wilkins, Polly
Abstract: This article explores the many more-than-human actors involved in crafting migrant (im)mobility across the Alps and the racialised (re)production of the borderscape as what I call a whitescape. Using cycling and hiking as embodied and mobile methodologies of encounter it examines the entanglement of landscapes, terrains, gradients, weather, water, and forests, alongside transport and tourist infrastructures: roads, railways, tunnels, bus routes, ski slopes, golf courses, hiking trails and cycling tracks in shaping how illegalised migrants encounter the Alpine Susa Valley/Hautes-Alpes border routes and how these ecologies are made political. Drawing on the work of Juanita Sundberg the article makes the case for posthumanism and political ecology in the study of borderscapes and illegalised migrant (im)mobility, while being sensitive to the racist dynamics of the nature/culture divide present in much posthumanist and political ecology scholarship. Therefore, while the article makes space for the role of more-than-human actors in borderscapes it also highlights the racialising work of these more-than-human entanglements in the following ways: through perpetuating dualist ontologies of nature/culture or nature/human from which illegalised migrants are linked to the natural, read pre-modern, world; and through producing illegalised migrants as 'bodies-out-of-place' in a political ecology that is concomitantly (re)produced as a whitescape.